Deiksis Dalam Siniar ‘Ketika Gen Z Jadi Dokter’ Raditya Dika - Fadya Khansa Hanum; Suyoto Suyoto; Asrofah Asrofah (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
The importance of analyzing deixis in profession-themed podcasts through a contextual pragmatic approach, highlighting the communication patterns of Generation Z in digital media, particularly in interactive and situational vodcast formats. This study aims to describe the forms and functions of person, place, and time deixis in the podcast video “When Gen Z Becomes a Doctor” on Raditya Dika’s YouTube channel, published on June 19, 2025. The research data consist of utterances by Raditya Dika as the interviewer and Dr. Iksanudin Qoti as the interviewee, obtained through a transcription process and analyzed using a descriptive qualitative method. The results show that person deixis is used to emphasize roles, relationships, and interactional positions among speakers. Place deixis functions to refer to both physical locations and conceptual spaces that emerge in narratives related to the medical field and the experiences of Generation Z. Meanwhile, time deixis is used to indicate the chronology of events, the span of experiences, and temporal markers within the flow of conversation. Overall, these three types of deixis play an important role in clarifying the context of utterances, constructing meaning relations, and creating the distinctive interactive and situational communication style of podcasts. This study contributes to enriching pragmatic studies, particularly regarding the use of deixis in the context of digital communication based on podcasts.